Graf Ramsey (5k_2, 2k_9)-Minimal - Permataputri, Nailul Yuni (AKTUARIA, 2025)
For given two graphs G and H, the notation F → (G,H) means that any red-blue coloring of all the edges of F contains a red copy of G as a subgraph or a blue copy of H as a subgraph. A graph F is Ramsey (G,H)-minimal if F \righttarrow (G,H) and for any edge e in F then F-e \nrightarrow (G,H). The class of all (G,H)-minimal graph, is denoted by R(G,H). In this research, we determined graphs in R(5K2,2K9).